If you were to move use the substitution method to solve the following system choose the new equation after the expression equivalent to ask from the second equation is subject to dig into the first equation.

2x-3y=-29
x+4y=13

A) 2(4y+13)-3y=-29
B) 2(-4y+13)-3y=-29
C) 2x-3(4y+13)=-29
D) 2x-3(-4y+13)=-29

Respuesta :

Solve x+4y = 13 for x by subtracting 4y from both sides.

We end up with x = -4y+13.

Since x and -4y+13 are the same, we can replace every x in the first equation with -4y+13

2x-3y = -29

2( x ) - 3y = -29

2( -4y+13 ) - 3y = -29 ... x is replaced with -4y+13

The answer is choice B